2002
DOI: 10.1046/j.0009-9163.2002.00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Inducible nitric oxide synthase gene and diabetic retinopathy in Asian Indian patients

Abstract: Nitric oxide, a signal transduction molecule, when modulated causes various diseases including diabetic retinopathy. In diabetes, allelic polymorphism of the inducible nitric oxide synthase (iNOS) gene is associated with retinopathy in the Northern Irish population. In the present study we investigated the Asian Indian population. One hundred and ninety-nine unrelated Asian Indian patients with 15 or more years of type 2 diabetes were divided into two groups: (a) diabetic retinopathy (DR) and (b) diabetic nonr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 42 publications
1
9
0
1
Order By: Relevance
“…A Gly82 Ser polymorphism is potentially interesting since it occurs at a predicted N-linked glycosylation motif in the AGE binding site, and may therefore influence the AGE-RAGE interactions(Hudson et al, 1998). This polymorphism was associated with a lower risk for development of DR in a case-control study with 100 affected patients and 100 controls, although the study design was rather poor(Kumaramanickavel et al, 2002 a). The finding is further supported by Hudson et al(Hudson et al, 2001).…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…A Gly82 Ser polymorphism is potentially interesting since it occurs at a predicted N-linked glycosylation motif in the AGE binding site, and may therefore influence the AGE-RAGE interactions(Hudson et al, 1998). This polymorphism was associated with a lower risk for development of DR in a case-control study with 100 affected patients and 100 controls, although the study design was rather poor(Kumaramanickavel et al, 2002 a). The finding is further supported by Hudson et al(Hudson et al, 2001).…”
mentioning
confidence: 72%
“…One of those studies examined the association between proliferative diabetic retinopathy and tumor necrosis factor-α (TNF-α) within the MHC class III region in T2DM (Hawrami et al, 1996). TNF-α is involved in the pathogenesis of DR by inducing a hypercoagulatory state through the effect on platelet-activating factors, thromboxin, and protein kinase C. Findings supporting the role of inflammation in the pathogenesis of DR have been described by Kumaramanickavel et al (Kumaramanickavel et al, 2002 b), who have demonstrated an association between a polymorphism in the inducible nitrate oxidase gene and DR in 199 Indian patients. The earliest detectable abnormality in retinal circulation is an increase in blood flow.…”
Section: Further Studies/pathomechanisms (Tables 6 -10)mentioning
confidence: 99%
“…Numerous studies have shown that genetic factors play a major role in susceptibility to DR. A number of genetic associations have been well validated and several genes are related to susceptibility to DR. These include aldose reductase (AKR1B1), VEGF, nitric oxide synthase, angiotensin‐converting enzyme and transforming growth factor‐β genes [17–21]. To our knowledge, the present study is the first to examine polymorphisms of the ICAM‐1 gene in Chinese patients with DR.…”
Section: Discussionmentioning
confidence: 99%
“…Later we worked on a pentanucleotide repeat poly-morphism (CCTTT)n in inducible NOS (iNOS) gene. We found a moderate association of two low risk alleles ((CCTTT)13&17) and a high risk allele ((CCTTT)13) for DR [8]. Recently, we also reported that the 27 bp intron4 VNTR of eNOS gene was not associated with DR in a population-based South Indian cohort, much to the contradiction of worldwide reports [9].…”
Section: Responsementioning
confidence: 99%